2012
DOI: 10.1183/09031936.00216011
|View full text |Cite
|
Sign up to set email alerts
|

Acetazolamide and chronic hypoxia: effects on haemorheology and pulmonary haemodynamics

Abstract: We tested the effect of acetazolamide on blood mechanical properties and pulmonary vascular resistance (PVR) during chronic hypoxia.Six groups of rats were either treated or not treated with acetazolamide (curative: treated after 10 days of hypoxic exposure; preventive: treated before hypoxic exposure with 40 mg?kg) and either exposed or not exposed to 3 weeks of hypoxia (at altitude .5,500 m). They were then used to assess the role of acetazolamide on pulmonary artery pressure, cardiac output, blood volume, h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 33 publications
0
25
1
Order By: Relevance
“…In the pulmonary circulation, hyperviscosity can have similarly detrimental effects. In a murine model of chronic mountain sickness, a disorder characterized by hypoxia-induced polycythemia and arterial desaturation, chronic hypoxia led to an increase in PVR which was both preventable and reversible via reduction in blood viscosity with acetazolamide [20]. Small studies in humans also suggest that the adverse hemodynamic effects of hyperviscosity are reversible, at least in the short term.…”
Section: Discussionmentioning
confidence: 99%
“…In the pulmonary circulation, hyperviscosity can have similarly detrimental effects. In a murine model of chronic mountain sickness, a disorder characterized by hypoxia-induced polycythemia and arterial desaturation, chronic hypoxia led to an increase in PVR which was both preventable and reversible via reduction in blood viscosity with acetazolamide [20]. Small studies in humans also suggest that the adverse hemodynamic effects of hyperviscosity are reversible, at least in the short term.…”
Section: Discussionmentioning
confidence: 99%
“…Each of these hemorheological parameters may affect the pulmonary vasculature. In animal models, increased blood viscosity and reduced RBC deformability have been shown to increase pulmonary vascular resistance, 9,26 and impaired RBC aggregation properties were demonstrated to impact microcirculation. 10 Multivariate analysis demonstrated that the RBC disaggregation threshold was the only parameter associated with the occurrence of ACS in SCC children.…”
Section: Discussionmentioning
confidence: 99%
“…6,7 Abnormal hemorheology may severely impact blood flow 8 as increased blood viscosity can raise vascular resistance both at the systemic and pulmonary levels. 9 Blood viscosity is modulated by the hematocrit, which can be very low in SCD due to hemolysis, and by the rheological properties of red blood cells (RBC), which are markedly altered in SCD by the presence of sickle hemoglobin, HbS. In addition, although poorly studied in SCD, 7 RBC aggregation may modulate blood flow in smaller blood vessels because increased RBC aggregation causes an accumulation of RBC in the central zone of flow (axial migration), resulting in a cell-poor layer near the vessel wall, and leading to decreased hematocrit of marginal blood streams (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…The fall in pulmonary vascular hindrance (curative by −27 % and preventive by −45 %) suggests that Acz could decrease pulmonary vessels remodelling under chronic hypoxia. The effect of Acz appears multifactorial, acting on erythropoiesis, pulmonary circulation, hemorheological properties and cardiac output [ 45 ].…”
Section: Adult Ha Nativesmentioning
confidence: 99%